Impact of physical exercise on the regulation of brain-derived neurotrophic factor in people with neurodegenerative diseases - Ana Romero Garavito; Valery Díaz Martínez; Estherz Juárez Cortés; José Vicente Negrete Díaz; José Vicente Negrete Díaz; Liliana Marcela Montilla Rodríguez (Frontiers in Neurology)
This review explores the impact of physical exercise on brain-derived neurotrophic factor (BDNF) and its relationship with neurodegenerative diseases. The key role of BDNF in maintaining brain health is highlighted, and recent studies are analyzed that indicate an increase in BDNF levels following physical activity, particularly in young adults. Additionally, the interaction between the BDNF Val66Met genetic polymorphism and exercise on cognitive function is examined. The review emphasizes the possibility of exercise as a complementary therapy for neurodegenerative diseases, although further research is required to fully understand its effects.